Социолого-статистический мониторинг в контексте взаимодействия социологии и статистики: понятие и структура - Кечина, Е. (Социология: теория, методы, маркетинг, 2008)
Sociological and statistical monitoring as a type of social research gets|receive| an ever more wide us age in different spheres of public life. The co-operation of sociology and statistics permits to combine the theoretical and methodological resources of sociology and statistics as well as empiric data within the process of social cognition. It is put into effect in methodological form, subject form, research form, informative form, and organizational form. The author try to consider in details the concrete sociological and statistical research within the program “Monitoring and estimation of situation for HIV/AIDS”, being realized in Republic Byelorussia since 2001 till now a days. The national system of monitoring and estimation of situation for HIV/AIDS is aimed to systematic obtaining, acquisition, analysis and granting information about measures facing the situation concerning spread of HIV/AIDS in the country. The program is intended to get indicators both on direct and latent developing processes in sphere of HIV/AIDS in respect to different regions and groups of population. Such an approach is conducive to prognosticate both positive and unfavorable tendencies in this sphere. The important part of the National system of monitoring and estimation of situation for HIV/AIDS is a study of the programs of influence efficiency.